Earthworms influence the production of above- and belowground biomass and the expression of genes involved in cell proliferation and stress responses in Arabidopsis thaliana - Jana, U; Barot, Sébastien; Blouin, Manuel; Lavelle, Patrick M.; Laffray, D; Repellin, A (Elsevier, 2010)
To better understand the complex mechanisms of action of earthworms on plants, we set up an experimental system using the model plant Arabidopsis thaliana (L.) Heynh, Aporrectodea caliginosa a common temperate earthworm and two types of soil with contrasted contents in organic matter and nutrients. Changes in plant biomass, biomass allocation to roots, leaves and stems and C/N ratios were related to variations in the expression of several plant genes involved in cellular division and stress responses and with earthworm-induced alterations in soil mineral status.